Do conteúdo a crítica: a produção sobre audiovisual do perfil cinema com crítica no Instagram - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The work aims to analyze the production and distribution of audiovisual content on the social media Instagram. Through this discussion, we seek to understand how the work of curating Instagram profiles contributes to an education on audiovisual with the public, based on na analysis of the “Cinema with Critics” profile. The research becomes relevant through the low number of studies on the production of content through social media such as Instagram and also by the theme having a social relevance for dealing more deeply with the importance of the platform in the transmission and production of content about audio-visual. The theoretical contribution is based on the culture of convergence (JENKINS), culture of connection (JENKINS; GREEN; FORD) and digital media (RECUERO). It is a qualitative, exploratory, descriptive and bibliographic research. As procedures adopted, we used a semi-structured interview with the profile holder Márcio Sallem, and a content analysis and observation of the profile production through the data collection carried out by a compound week. From these methodological procedures it was possible to identify that the content of the profile has plurality as its main characteristic and manages to cover several audiovisual themes in a critical way but encouraging knowledge and learning about the theme directed to followers.
Keywords: Mídia social; Cinema; Crítica; Instagram (Firma); Recursos audiovisuais; Social media; Criticism; CNPQ::CIENCIAS SOCIAIS APLICADAS